Analisis Program Sertifikasi Halal Sebagai Penerapan Etika Bisnis Islam Pada Usaha Mikro Kecil Di Kota Jambi - Roza Alfian; Lucky Enggrani Fitri; Ridhwan Ridhwan (JOURNAL OF SHARIA ECONOMICS, 2024)
The purpose of this research is to determine and analyze the government's role in the halal certification program, to determine and analyze the response of business actors and consumers to the halal certification program and to determine and analyze the relationship between the halal certification program and the application of Islamic business ethics. The research method used is qualitative. The data sources used in this research consist of two types of data, namely primary data and secondary data. The data collection techniques used in this research are direct observation, interviews and documentation. The results of this research show that: (1) The government plays an active role in optimizing the halal certification program for micro and small business actors in Jambi City by opening a free halal certification program (SEHATI) from January 2 2023 to October 17 2024 with a target of 1 million free halal certification quota with self-declare mechanism. (2) The response of business actors to the halal certification program in Jambi City is very positive. Halal certification is very important for business actors, because with halal certification, they can market their products to super markets or even souvenir centers. This of course has a positive impact because it can increase the selling value of the product. The consumer response to the halal certification program in Jambi City was welcomed positively, because with the halal label, consumers do not need to worry about the ingredients contained in it which have been confirmed to be halal. (3) The relationship between the halal certification program and the application of Islamic business ethics in the form of the main principles in Islamic business ethics in the form of, Tauhid, balance, free will and responsibility has been implemented by business actors. So apart from complying with government regulations with the existence of Law No. 33 of 2014 concerning Halal Product Guarantees, business actors also apply the principles of business ethics in running their business